2022
DOI: 10.30587/ghidzamediajurnal.v4i1.4529
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Intake Zat Gizi Makro, Zat Besi, Dan Vitamin C Dengan Kadar Hemoglobin Siswi Sma Di Kecamatan Kebomas

Abstract: Anemia is a condition where the number of erythrocytes or the amount of hemoglobin is below the normal value standard, which is more at risk for adolescent girls. The purpose of this study was to analyze the relationship between intake of macronutrients, iron, and vitamin C with hemoglobin levels of high school students in Kebomas District. This research method uses analytic observational research. The population as many as 115 high school students in Kebomas sub-district were taken using cluster random sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Research at SMAN 1 Manyar Gresik resulted in a significant relationship between vitamin C intake and Anemia with a p-value=0.000 20 . Then, research conducted at SMAN 1 Kebomas Gresik also showed a notable relationship between vitamin C intake and the incidence of Anemia with a p-value=0.028 21 . Female students with Anemia had inadequate vitamin C intake, with an average intake of 6.8 milligrams, which is significantly less than the RDA standard; therefore, their Hb levels are below normal Hb.…”
Section: Bivariate Analysis Resultsmentioning
confidence: 97%
“…Research at SMAN 1 Manyar Gresik resulted in a significant relationship between vitamin C intake and Anemia with a p-value=0.000 20 . Then, research conducted at SMAN 1 Kebomas Gresik also showed a notable relationship between vitamin C intake and the incidence of Anemia with a p-value=0.028 21 . Female students with Anemia had inadequate vitamin C intake, with an average intake of 6.8 milligrams, which is significantly less than the RDA standard; therefore, their Hb levels are below normal Hb.…”
Section: Bivariate Analysis Resultsmentioning
confidence: 97%
“…Iron intake is essential for the synthesis of hemoglobin. A sufficient iron intake will not inevitably lead in enough hemoglobin production if it is not balanced with the presence or participation of other nutrients [37]. Nutrients have a significant role in anemia, with iron being the most important of the nutrients involved.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C merupakan enhancer yang berguna untuk membantu penyerapan zat besi nonheme dengan cara mengubah jenis zat besi menjadi bentuk yang mudah diserap (Masthalina, 2015). Penelitian yang dilakukan oleh Pradanti (2015) dan Choiriyah (2015), menunjukkan hubungan kecukupan vitamin C dan zat besi dengan kadar hemoglobin. Transportasi protein dalam tubuh dan penyerapan besi yang dilakukan oleh vitamin C, dapat mempengaruhi jumlah yang tersedia dalam tubuh.…”
Section: Pendahuluanunclassified